Digital-Based Public Service Transformation through the SIAPkerja Application at the Indonesian Ministry of Manpower (Five Dimensional Service Quality Analysis) - Andhani, Dewi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
The digital era has encouraged the Ministry of Manpower of the Republic of Indonesia to launch SIAPkerja (Sistem Informasi dan Aplikasi Pelayanan Ketenagakerjaan) as an integrated platform for employment services. This study evaluates the transformation of public services through SIAPkerja using the five dimensions of public service quality (tangible, reliability, responsiveness, assurance, empathy) as an analytical framework. The method used is descriptive qualitative with data collection techniques of in-depth interviews, participatory observation, and documentation. The results show that SIAPkerja improves the accessibility and responsiveness of labour services, although it still faces challenges such as limited digital infrastructure in remote areas. The implementation of SIAPkerja also plays a role in supporting the principles of good governance through data integration and regular monitoring by the Ministry. This study concludes that SIAPkerja has improved the quality of technology-based public services, but recommendations for improving human resource capacity and infrastructure are still needed.